Pancasila as an Identity That Forms National Character: Analysis of the Philosophy of Indonesian Education (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The development of the education system must be in line with the main goals of education in a country. This research aims to analyze the role of educational philosophy in the formation of national identity contained in the values of Pancasila as identity and formation of national character. Methodology: This research uses a qualitative approach to understand social phenomena as a whole. This research method is designed to collect structured information and is in accordance with the objective of analysis regarding the role of educational philosophy in the formation of national identity. Main Findings: Analysis of educational philosophy in the formation of Indonesian national identity emphasizes the need to pay sufficient attention to the education of national values. Pancasila is not only the basis of the way of life for the Indonesian people, but also the basis for the guidelines for national and state life for all Indonesian citizens. Novelty/Originality of this study: Based on the literature study carried out, it can be concluded that Educational Philosophy is a deep thought about education that originates from philosophy, where Pancasila is the nation's way of life that influences daily life, so that the Indonesian national education system naturally reflects and is based on the identity of Pancasila. This research aims to ensure that all elements of education are able to maintain Pancasila values so that they continue to be taught in education because they are the identity of the Indonesian nation.